Comparative Prediction of Plasma Concentration Blood Brain Barrier Penetration Intestinal Absorption and Skin Diffusion of Diclofenac Sodium and its Complex with Cow s Ghee in Swiss Albino Mice - Bawankar, Ram D (International Journal of Pharmaceutical & Biological Archive, 2016)
Comparative Prediction of Plasma Concentration Blood Brain Barrier Penetration Intestinal Absorption and Skin Diffusion of Diclofenac Sodium and its Complex with Cow s Ghee in Swiss Albino Mice